A study on assessment of the length of styloid process in digital panoramic radiographs - Nikita Gupta; Mubeen Khan; Laxmi Gurunath Doddamani; Nisha Kampasi; Neera Ohri (Wolters Kluwer Medknow Publications, 2015)
Introduction: The styloid process (SP) is an anatomical structure whose clinical importance is not well understood. Aims and Objectives: This study aimed to study the type of SP as per Langlais' classification and to assess the feasibility of digital panoramic radiographs in measuring the length of SP. Materials and Methods: Eighty digital panoramic radiographs of patients with dental problems were retrieved from archives of our department as soft copies. The radiographs were taken using a digital panoramic system. The radiographic length of SP was measured on both sides using measurement toolbars on accompanying analysis software. The type of elongation patterns of SP was classified as per Langlais' classification. Finally, the data were subjected to statistical analysis. Results: The average length of the left and right side SPs was 29.1882 ± 6.86 and 28.16 ± 6.44, respectively. Majority of patients were found to be asymptomatic, and Langlais' Type I elongated SP was more common than others. Conclusion: Digital panoramic radiographs are valuable tools in early detection of elongated SP. Digital radiographs help in avoiding a misdiagnosis of tonsillar pain or pain of dental, pharyngeal, or muscular region.